Failing Firm Defense a la ecuatoriana. Algunos aportes y reflexiones sobre la nueva excepción de empresa en crisis - Navarrete Serrano, Mario (2020)
On April 20, 2020, the Superintendence of Market Power Control published Resolution SCPM-DS-2020-018 establishing a fast-track process to investigate certain operations subject to the ex-ante notification regime. What will be explored in this article is one of the cases that qualify to benefit from the fast-track process: the failing-firm defense exception.In summary, the Superintendence of Market Power Control has said that it will now take less time to review operations that target a company in economic difficulties, and it outlines the material parameters it will use to guide that decision. How-ever, such inclusion brings with it much more than it appears.